Whole-Genome Sequencing Identified KCNJ12 and SLC25A5 Mutations in Port-Wine Stains - Chen, Kai; Hu, Yan-Yan; Wang, Lin-Lin; Xia, Yun; Jiang, Qian; Sun, Lan; Qian, Shan-Shan; Wu, Jin-Zhao; Chen, Liu-Qing; Li, Dong-Sheng (Frontiers in Medicine, 2022)
Port-Wine Stains (PWS) are a congenital capillary malformed disorder and are caused by a lot of somatic mutations that disrupt vascular development. However, the underlying genetic mutations in the pathogenesis of PWS has not yet been fully elucidated. To understand PWS genetic variations and investigate novel genetic mutations, we extracted genomic DNA from four sporadic PWS patients and then performed whole genome sequencing (WGS). Using SIFT, PolyPhen2, Mutation Assessor, MetaSVM to identify candidate genetic mutations and Sanger sequencing to confirm the identified variants. We found a previously reported GNAQ mutation c.548G>A, p.Arg183Gln in one case, whereas no such mutation was found in other three samples. Moreover, six novel somatic mutations in three genes, including KCNJ12, SLC25A5, POTEE, were found in these four samples. Importantly, Sanger sequencing also verified the KCNJ12 (c.415G>A, p.Glu139Lys) and SLC25A5 (c.707G>C, p.Arg236Pro) mutations in other five sporadic PWS patients, with the frequency of 60% (3 of 5) and 40% (2 of 5), respectively. Thus, we present here the first time that reveals two novel somatic mutations, KCNJ12 and SLC25A5, in the sporadic PWS patients. These findings highlight the genetic polymorphism of PWS and provide potential clinical prediction targets for this disease.